Physiognomy, Passions of the Soul and Moral Assessment. An Approach to Marin Cureau de La Chambre and René Descartes - Sánchez Berrocal, Alejandro (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2017)
This article aims to illustrate the development of physiognomy following one of its central themes: moral characterisation. This work deals with the origins of the discipline until the proliferation of works that, during the 16th and 17th centuries, approached the so-called «passions of the soul» from such seemingly disparate points of view as philosophy, optics, comparative anatomy, astrology and medicine. To conclude, two opposite perspectives on the treatment of emotions or «passions of the soul» are discussed: one by René Descartes and another by philosopher-physician Marin Cureau de La Chambre.
Keywords: physiognomy; passions of the soul; moral; Baroque; Descartes.